2009
DOI: 10.1037/a0016375
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of individual differences in strategic retrieval processing.

Abstract: Processes engaged when information is encoded into memory are an important determinant of whether that information will be recovered subsequently. Also influential, however, are processes engaged at the time of retrieval, and these were investigated here by using event-related potentials (ERPs) to measure a specific class of retrieval operations. These operations were revealed by contrasts between ERPs elicited by new (unstudied) test items in distinct tasks, the assumption being that these contrasts index ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
35
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 35 publications
9
35
1
Order By: Relevance
“…This effect was most pronounced between 300 and 1,000 ms poststimulus and was broadly distributed over the scalp. This effect is thought to reflect retrieval cue processes that maximize the likelihood of retrieving targeted memory representations in each test phase, in line with the notion that participants can, in principle, perform the exclusion task on the basis of recovering target items alone (Bridger et al, 2009;Herron & Rugg, 2003). Support for this conjecture comes from experiments that have reported characteristically similar retrieval orientation effects in item Study phase Test phase Fig.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…This effect was most pronounced between 300 and 1,000 ms poststimulus and was broadly distributed over the scalp. This effect is thought to reflect retrieval cue processes that maximize the likelihood of retrieving targeted memory representations in each test phase, in line with the notion that participants can, in principle, perform the exclusion task on the basis of recovering target items alone (Bridger et al, 2009;Herron & Rugg, 2003). Support for this conjecture comes from experiments that have reported characteristically similar retrieval orientation effects in item Study phase Test phase Fig.…”
mentioning
confidence: 57%
“…Memory performance was lower in the imagined target condition, and frontal ERP retrieval orientation effects were larger for those participants who showed a greater memory performance difference between the imagined and perceived target conditions. This pattern comprises an important link between the adoption of specific retrieval orientations and recognition memory performance (see Bridger et al, 2009, for a comparable relationship) and highlights the influential role of the engagement of certain retrieval orientations on memory performance. Influential processes of this kind may also be sensitive to reward manipulations, and may thus provide one locus by which reward modulates memory performance.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…source-constrained searches) but does not speak to the question of whether source-constrained searches yield source-constrained retrieval. Bridger et al (2009) and Bridger and Mecklinger (2012) found correlations across subjects between (a) ERP indicators of constrained search on new recognition probes and (b) recognition accuracy. They described that finding as "strong evidence that this class of retrieval processing operations benefits the accuracy of memory judgments" (Bridger et al, 2009(Bridger et al, , p. 1175.…”
mentioning
confidence: 99%
“…Bridger et al (2009) and Bridger and Mecklinger (2012) found correlations across subjects between (a) ERP indicators of constrained search on new recognition probes and (b) recognition accuracy. They described that finding as "strong evidence that this class of retrieval processing operations benefits the accuracy of memory judgments" (Bridger et al, 2009(Bridger et al, , p. 1175. Thus, Bridger et al spoke directly to the issue of central interest here, and claimed that their results demonstrate source-constrained retrieval.…”
mentioning
confidence: 99%